Screening and evaluation of antioxidant activities of selected naphthalene compounds - Ozen, Tevfik; Macit, Mustafa; Toka, Mehmet (Penerbit Universiti Kebangsaan Malaysia, 2018)
The antioxidant activities of twelve naphthalene compounds containing (E)-1-((3-iodophenylimino)methyl) naphthalen-2-ol (NAPH1), (E)-1-((3-bromophenylimino) methyl) naphthalen-2-ol (NAPH2), E)-1-((4-bromo-2-(trifluoromethoxy) phenylimino) methyl) naphthalen-2-ol, (E)-1-((4-bromo-2-(trifluoromethoxy) phenylimino) methyl)naphthalen-2-ol (NAPH3), (E)-1-((2-methoxy-5-(trifluoromethyl) phenylimino) methyl) naphthalen-2-ol (NAPH4), (E)-1-((naphthalen-2-ylimino) methyl) naphthalen-2-ol (NAPH5), (E)-1-((2-bromo-3-methylphenylimino) methyl) naphthalen-2-ol (NAPH6), (E)-N-((2-ethoxynaphthalen-1-yl)methylene)-3-methylaniline (NAPH7), (E)-4-ethoxy-N-((2-ethoxynaphthalen-1-yl) methylene) aniline (NAPH8), (E)-N-((2-ethoxynaphthalen-1-yl) methylene) naphthalen-1-amine (NAPH9), (E)-1-(2,5-difluorophenyl)-N-((2-ethoxynaphthalen-1-yl) methylene) methanamine (NAPH10), (E)-N-((2-ethoxynaphthalen-1-yl) methylene)-4-fluoroaniline (NAPH11), (E)-N-((2-ethoxynaphthalen-1-yl)methylene)-2-ethylaniline (NAPH12) were investigated in vitro by antioxidant activity (phosphomolybdenum assay), reducing power, H2O2 scavenging activity, metal chelating effects and lipid peroxidation. Scavenging activities of the naphthalen compounds were tested against 1,1-diphenyl-2-picrylhydrazyl, hydroxyl and superoxide anion radicals. Most of them are potent antioxidant, radical superoxide anion scavengers and in vitro inhibition of lipid peroxidation. The compounds; NAPH5, NAPH10 and NAPH12 were found to exhibit promising antioxidant profiles at 10 and 50 mM concentrations. Among these, NAPH5 at higher concentration was the most active compound in inhibiting lipid peroxidation as shown in the homogenates of kidney, heart and spleen. The presented results validate that NAPH5, NAPH10 and NAPH12 can be possessed as a source of antioxidant potential and a rich source of synthetic antioxidant for medicinal or foods.